2016
DOI: 10.1007/s10750-016-2920-6
|View full text |Cite
|
Sign up to set email alerts
|

Hydrologic connectivity driven natural stream fish assemblages in mountain streams in the Yangtze River basin: implications for stream fish conservation in monsoonal East Asia

Abstract: The East Asian monsoon and related seasonal rain belts are assumed to be significantly variable at intraseasonal, interannual, and interdecadal time scales, and largely determine the hydrology and ecological processes of the streams and rivers in this region. This study investigated the spatiotemporal variation in fish assemblages and the relative importance of local habitat and regional landscape variables in two protected streams in the middle Yangtze River basin. We hypothesized that the stream fish assembl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(39 citation statements)
references
References 88 publications
0
35
4
Order By: Relevance
“…Recently, two new records of Schizothorax, S. prenanti Tchang and S. griseus Pellegrin, were reported from the Lishui River (He et al 2016). In addition, an endemic blind stone loach, Triptophysa xiangxiensis Yang Yuan & Liao, occurs in the adjacent drainage, upper Youshui River, another tributary of Lake Dongting .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, two new records of Schizothorax, S. prenanti Tchang and S. griseus Pellegrin, were reported from the Lishui River (He et al 2016). In addition, an endemic blind stone loach, Triptophysa xiangxiensis Yang Yuan & Liao, occurs in the adjacent drainage, upper Youshui River, another tributary of Lake Dongting .…”
Section: Discussionmentioning
confidence: 99%
“…The present study showed fish assemblages in streams of the Ren River basin were structured by a combination of large-scale landscape factors (e.g., altitude and C-link) and local habitat features (e.g., channel width, water temperature, and depth), among which, landscape factors acted as the most important contributor in both wet and dry seasons. The importance of landscape position in structuring fish assemblages has been demonstrated by numerous studies (e.g., Fairchild et al, 1998;He et al, 2017;Li et al, 2012;Smith & Kraft, 2005;Zhu et al, 2017). With regard to landscapes therefore, streams should be regarded as connected networks with a definable "network geometry," rather than a linear hierarchy most represented by stream order (Benda et al, 2004;Smith & Kraft, 2005).…”
Section: Environmental Effects On Fish Assemblagesmentioning
confidence: 99%
“…Osborne and Wiley ( 1992 ) observed D‐link explained the greatest portion of the variance in fish species richness and suggested downstream processes significantly influence the structure of fish assemblages. In addition, seasonal variations in environmental conditions caused by periodic flooding are expected to have significant impacts on stream fish assemblages (He et al., 2017 ; Ostrand & Wilde, 2002 ). Flooding can increase the diversity and availability of habitat structures and food resources and then lead to changes in fish assemblages between dry and wet seasons (Araújo et al., 2009 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations